Pendugaan Kadar Air di Lahan Tanaman Kopi Malang Selatan dengan Penginderaan Jauh - Septrial Arafat; Muhammad Iqbal Fauzan; Anita Dwy Fitria (Universitas Teuku Umar, 2023)
Soil water availability is the basis for plant growth, so its availability is the main key for coffee plants growing in South Malang. Fluctuations in groundwater content, especially in the dynamics of climate change, must be managed so that plant water needs are always met, while remote sensing is able to provide aspects of estimating the condition of soil water content in coffee plantations in South Malang. This research was conducted from July 2019 to October 2019. The water content in coffee plantations can be estimated by combining the vegetation index value and soil surface temperature because coffee plants have shade. The method used in this research is to make a tentative map obtained from the overlay between the Normalized Difference Vegetation Index (NDVI) and Land Surface Temperature (LST) maps, the data is then regressed with the field results. The selection of research locations is based on the area of the coffee plantation using the smallest pixel, which is in an area of 3 km square meters. Each location of the research location was carried out four times for sampling the soil moisture content. The results showed that the correlation value between water content and the estimation results had a correlation of 0.814, with a regression value of 0.663 and a probability value of 0.9226.